Impact of the WellCheck smartphone app linked to electronic health records on clinical outcomes in patients with type 2 diabetes: Study protocol for primary care-based, prospective, multicenter, cluster-randomized, pragmatic clinical trials - Hyunji Sang; Sunyoung Kim; Jiyoung Hwang; Selin Woo; Yerin Hwang; Jaewon Kim; Seohei Lee; Dong Keon Yon; Sang Youl Rhee (PLoS ONE, 2025)
Diabetes, obesity, and dyslipidemia are significant contributors to cardiovascular diseases, necessitating effective strategies to manage blood glucose, blood pressure, and lipid levels through lifestyle interventions and pharmacotherapy. This study aims to assess the glycemic control and metabolic health outcomes achieved over 24 weeks with the use of the “WellCheck” digital healthcare application in patients diagnosed with type 2 diabetes mellitus (T2D) within real-world primary care settings. This is a primary care-based, prospective, multicenter, cluster-randomized pragmatic trial. Eligible participants include adults aged 19–80 with T2D who are treated with or planning to be treated with Envlo (enavogliflozin) or Envlomet (enavogliflozin/metformin). WellCheck links a mobile application for patients with a web platform for physicians and integrates with electronic health records to support the management of diabetes and hypertension. The primary outcome is the change in glycated hemoglobin levels at 24 weeks from baseline. We will conduct cluster randomization by grouping 24 participating primary care centers according to basic characteristics, such as the treating physician’s age (above or below 45 years) and the clinic’s location (metropolitan or non-metropolitan areas). The “App+Physician Support” group will use the WellCheck app for comprehensive digital monitoring and receive feedback supported by an investigator (primary care physician), and the “App-Only” group will rely on the WellCheck app for independent self-management without direct physician assistance. This study aims to explore the effectiveness of WellCheck app in improving glycemic control and metabolic outcomes, providing valuable insights into its potential as a digital tool for managing T2D. The wide age range of participants and cluster randomization of primary care centers into the intervention and control groups enhance the generalizability and robustness of the study, reducing bias and enabling a meaningful comparison of outcomes in diverse healthcare settings. Trial registration ClinicalTrials.gov NCT06419816. Registered on 14 May 2024.